The Development of Reproducible and Selective Uric Acid Biosensor by Using Electrodeposited Polytyramine as Matrix Polymer - Manihar Situmorang; Isnaini Nurwahyuni (Universitas Gadjah Mada, 2017)
A versatile method for the construction of reproducible and high selective uric acid biosensor is explained. Electrodeposited polytyramine is used as biosensor matrixes due to its compatibility to immobilize enzyme uric oxidase in the membrane electrode. The precise control over the charge passed during deposition of polytyramine allows concomitant control over the thickness of the deposited enzyme layers onto the surface of the electrode. The uric acid biosensor showed a sensitive response to uric acid with a linear calibration curve lies in the concentration range of 0.1–2.5 mM, slope 0.066 µA mM-1, and the limit detection was 0.01 mM uric acid (S/N = 3). The biosensor shown excellent reproducibility, the variation between response curves for uric acid lies between RSD 1% at low concentrations and up to RSD 6% at saturation concentration. Uric acid biosensor is free from normal interference. The biosensor showed good stability and to be applicable to determine uric acid in real samples. Analysis of uric acid in the reference standard serum samples by the biosensor method are all agreed with the real value from supplier. Standard samples were also analyzed independently by two methods: the present biosensor method and the standard UV-Vis spectrophotometry method, gave a correlation coefficient of 0.994. This result confirms that the biosensor method meets the rigid demands expected for uric acid in real samples.